Compassionate use of long‐acting cabotegravir plus rilpivirine for people living with HIV‐1 in need of parenteral antiretroviral therapy. Issue 2 (9th August 2022) - D'Amico, Ronald; Cenoz Gomis, Santiago; Moodley, Riya; Van Solingen‐Ristea, Rodica; Baugh, Bryan; Van Landuyt, Erika; Van Eygen, Veerle; Min, Sherene; Cutrell, Amy; Foster, Caroline; Chilton, Daniella; Allard, Sabine D.; et al.
Abstract: Objectives: Physicians could request compassionate use of oral and long‐acting (LA) cabotegravir + rilpivirine for people living with HIV‐1 under a single‐patient request programme supported by ViiV Healthcare and Janssen. Outcomes are reported. Methods: Eligibility criteria included need for parenteral therapy, no primary resistance mutations to cabotegravir or rilpivirine, and established retention in care. Demographic, efficacy, and safety data were obtained from standardized programme applications and quarterly clinical updates. Individuals received a loading dose of LA cabotegravir 600 mg + rilpivirine 900 mg, followed by LA maintenance doses of 400 mg/600 mg every 4 weeks; some received lead‐in oral cabotegravir and rilpivirine. Results: Through July 2020, 35 people living with HIV‐1 had data available. The most frequent reason for compassionate use request was chronic non‐adherence due to psychological conditions (n = 15). Of 35 people living with HIV‐1, 28 had detectable viremia (median viral load 60 300 copies/mL) and seven were virologically suppressed at programme entry; 16/28 and 6/7 achieved or maintained virological suppression at data cutoff, respectively. Seven people living with HIV‐1 discontinued for incomplete virological response, six with detectable viremia at initiation; six and four had new reverse transcriptase and integrase mutations at discontinuation, respectively. Six non‐fatal serious adverse events were reported, two considered possibly treatment related. Four deaths were reported; none were treatment related. One individual reported two pregnancies and continued LA dosing. Conclusions: Most people living with HIV‐1 had advanced disease and achieved (16/28) or maintained (6/7) virological suppression with LA therapy. Cabotegravir LA + rilpivirine LA as compassionate use provided a valuable treatment option for individuals with adherence issues with oral therapy and advanced disease.